INTEGRATION OF RENEWABLE ENERGY OF SOLAR PV AND UTILITY PLN GRID FOR THE OPTIMAL CHARGING OF ELECTRIC VEHICLES THE RESIDENTIAL SCALE - Ansori, Aris; Adiwibowo, Priyo Heru; Siregar, Indra Herlamba; Wailanduw, Grummy; Anwar, Saiful (LPPM Universitas Jambi, 2026)
This study proposes and evaluates an off-grid hybrid electric vehicle (EV) charging system that integrates a 5 kWp solar photovoltaic (PV) array, a 5.5 kW PLN grid connection, and a 12 kWh battery energy storage system controlled by an automatic transfer switch (ATS). The system is designed to maximize solar PV utilization while minimizing dependence on the PLN grid during peak demand periods, thereby reducing carbon emissions, electricity consumption, and charging costs. Experimental testing was conducted using two EV types: a Viar NX electric motorcycle (1.338 kWh battery capacity) and a Wuling Air EV Long Range electric car (26.7 kWh battery capacity). Both vehicles were charged from 30% to 100% state of charge under different operating conditions. Energy generation from the PV system, battery storage performance, and PLN grid contribution were monitored using kWh meters and data loggers. Performance evaluation considered energy production, electricity cost savings, and economic feasibility. Results indicate that the PV system generated an average of 12.38 kWh/day for EV charging. During the dry season, monthly PV generation ranged from 368.40 to 383.78 kWh, while production declined to approximately 286.75 kWh during the rainy season because of reduced solar irradiation. The battery storage and PLN grid effectively compensated for low PV output, ensuring uninterrupted charging. Solar PV supplied approximately 48.06% of the total EV charging energy demand, with charging performance strongly influenced by daytime charging schedules and favorable weather conditions. These findings confirm the technical and economic feasibility of residential-scale hybrid solar PV-based EV charging systems.